2017
DOI: 10.1111/tmi.13011
|View full text |Cite
|
Sign up to set email alerts
|

Sustained adoption of water, sanitation and hygiene interventions: systematic review

Abstract: Abstractobjective To understand factors that influence sustained adoption of water, sanitation and hygiene (WASH) technologies or behaviours.methods Systematic review of the current literature. Articles were gathered from databases of peerreviewed articles and grey literature, and screened for relevance. After exclusion, we created a descriptive map of 148 articles and analysed in-depth 44 articles that had an explicit focus on promoting or evaluating sustained adoption or programme sustainability. Twenty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
4
43
1
Order By: Relevance
“… 12 , 15 Therefore, the promotion of soapy water as a hand cleansing agent with 1.5-L bottles as a dispenser was low-cost, acceptable, and feasible for handwashing in low-income urban communities, and has the potential for sustained adoption. 23 This mirrors the findings of a study conducted in rural Bangladesh. 18 In addition, a trial among low-income urban communities in Dhaka found soapy water was equally effective as bar soap in removing indicator organisms from hands and more effective than water alone.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“… 12 , 15 Therefore, the promotion of soapy water as a hand cleansing agent with 1.5-L bottles as a dispenser was low-cost, acceptable, and feasible for handwashing in low-income urban communities, and has the potential for sustained adoption. 23 This mirrors the findings of a study conducted in rural Bangladesh. 18 In addition, a trial among low-income urban communities in Dhaka found soapy water was equally effective as bar soap in removing indicator organisms from hands and more effective than water alone.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, this innovation has the potential to increase handwashing with soap as part of large-scale national promotions. Important areas for future research include lowering the cost of behavior change promotion potentially by using mass media, identifying systematic definitions of sustained adoption and methodology to rigorously evaluate water and sanitation interventions, 23 and evaluating sustainability and sustained behavioral impact of such interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review found the sustainability of WASH interventions is frequently inadequately evaluated [ 32 ]. One study evaluated the sustainability of an existing development HWT with chlorine program that expanded after the Haiti earthquake and cholera outbreak [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of WASH behavioural models concluded that existing approaches have overemphasised hypothetical psychological variables and should instead focus on aspects of the physical and natural environment, as well as on technological features (Dreibelbis et al 2013). However, in a more recent systematic review, psychological factors were considered key for the maintenance of WASH behaviour change, alongside technological and contextual factors (Martin et al 2018). In fact, in another review it was reported that sociopsychological variables explained 62% of safe water drinking behaviours, while contextual factors were said to contribute little by way of explanation (Lilje and Mosler 2018).…”
Section: Existing Formulations Of Wash Behavioursmentioning
confidence: 99%